2017
DOI: 10.1093/mnras/stx3188
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Herschel DEBRIS Sun-like star sample

Abstract: This paper presents a study of circumstellar debris around Sun-like stars using data from the Herschel DEBRIS Key Programme. DEBRIS is an unbiased survey comprising the nearest ∼90 stars of each spectral type AM. Analysis of the 275 F-K stars shows that excess emission from a debris disc was detected around 47 stars, giving a detection rate of 17.1 +2.6 −2.3 per cent, with lower rates for later spectral types. For each target a blackbody spectrum was fitted to the dust emission to determine its fractional lumi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(142 citation statements)
references
References 60 publications
(59 reference statements)
9
131
1
Order By: Relevance
“…We take the same approach as for A stars, and we simulate a population of FGK stars following the results by Sibthorpe et al (2018) that used both Spitzer and Herschel FIR photometry of 275 FGK stars to fit a collisional evolution model, similar to Wyatt et al (2007b). That study found best-fit parameters A = 5.5 × 10 5 , B = 0.1 and γ = −1.7.…”
Section: Solar-type Starsmentioning
confidence: 99%
“…We take the same approach as for A stars, and we simulate a population of FGK stars following the results by Sibthorpe et al (2018) that used both Spitzer and Herschel FIR photometry of 275 FGK stars to fit a collisional evolution model, similar to Wyatt et al (2007b). That study found best-fit parameters A = 5.5 × 10 5 , B = 0.1 and γ = −1.7.…”
Section: Solar-type Starsmentioning
confidence: 99%
“…Despite its relatively low total mass, dust in circumstellar debris disks is readily detected because of its high specific cross section. Current far-infrared detection rates are as high as ∼ 20 % for nearby stars (Eiroa et al 2013;Montesinos et al 2016;Sibthorpe et al 2018), indicating how ubiquitous these disks are. Akin to the Edgeworth-Kuiper belt in the Solar system, debris disks are often found at distances of tens or more than one hundred au from their host stars (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This constraint is consistent with analyses using Herschel and Spitzer. Sibthorpe et al (2017); Eiroa et al (2013); Trilling et al (2008), for instance, have measured hundreds of debris disks around a sample of typically brighter stars using such surveys, and find f disk in the range of 10-30% .…”
Section: Discussionmentioning
confidence: 99%